Expert evaluation of mobile health apps for breast cancer management: a feature-based analysis using the Mobile Application Rating Scale (MARS) - Ghazaleh Mohammadi Mogharab; Reza Khajouei; Narges Norouzkhani; Zahra Esmaeili; Fatemeh Zahra Bagheri; Mohammad Reza Mazaheri Habibi (BMC Health Services Research)
Abstract Background Breast cancer remains a major global health issue, with millions of cases diagnosed annually and limited diagnostic and treatment options, particularly in developing countries. This study aimed to evaluate the quality of breast cancer mobile health (m-health) applications using the Mobile Application Rating Scale (MARS) to guide healthcare stakeholders and patients identify high-quality mobile health applications that meet their needs. Methods A cross-sectional study was conducted in Mashhad, Iran, from February to July 2023, targeting breast cancer apps. Relevant apps were identified through comprehensive searches in databases and app stores based on predefined inclusion criteria. Four health information technology experts independently assessed the apps using MARS and the Feature-based Application Rating Method (FARM), with discrepancies resolved through discussion to ensure reliability. Data analysis included calculating mean scores, testing for data normality, and examining correlations between MARS and FARM dimensions using Spearman’s correlation. Results Of the 453 identified apps, 44 met the inclusion criteria. The average MARS and FARM score was 3.3 out of 5, indicating moderate quality. The functionality dimension scored highest at 4.1, reflecting strong technical performance; however, deficiencies in informational quality negatively impacted user trust and satisfaction. A strong correlation (r = 0.806) was observed between engagement and other quality dimensions, indicating variability in user engagement across apps. Conclusions While many breast cancer apps demonstrated high technical functionality, significant informational gaps reduced user trust and satisfaction. This study underscores the need for regulatory standards to ensure reliable content in breast cancer apps. Future app development should prioritize user engagement and informational quality to better meet patient needs.